Examining how study teams manage different viewpoints and priorities in patient‐centered outcomes research: Results of an embedded multiple case study - Maureen E. Maurer; Tandrea Hilliard‐Boone; Karen Frazier; Laura Forsythe; Rachel Mosbacher; Kristin L. Carman (Health Expectations, 2023)
Abstract Introduction Limited evidence exists about which patient and stakeholder engagement practices support or hinder study teams as they negotiate different viewpoints in decisions about the design and conduct of patient‐centered outcomes research. Methods We applied a multiple‐embedded descriptive case study design for six studies funded by the Patient‐Centered Outcomes Research Institute (PCORI). We interviewed 32 researchers and stakeholder partners, including patients, caregivers and clinicians, and reviewed documents related to each study (e.g., publications, and progress reports submitted to PCORI). Findings Overall, researchers reported that incorporating different viewpoints was a strength or opportunity to learn rather than something to be avoided or dreaded. Across cases, different viewpoints and priorities, often related to ethical or pragmatic considerations, emerged between researchers and stakeholders, between stakeholder groups (e.g., patients and clinicians) or within groups (e.g., amongst researchers). Examples of navigating different viewpoints arose across study phases. The length of time to resolve issues depended on how strongly people disagreed and the perceived importance or impact of decisions on the study. All cases used collaborative decision‐making approaches, often described as consensus, throughout the study. Interviewees described consensus as using negotiation, compromise or working towards an agreeable decision. To encourage consensus, cases actively facilitated group discussions with an openness to diverse opinions, remained flexible and open to trying new things, referenced a ground rule or common goal and delegated decisions to partners or smaller workgroups. When viewpoints were not easily resolved, cases used different approaches to reach final decisions while maintaining relationships with partners, such as elevating decisions to leadership or agreeing to test out an approach. No one engagement structure (e.g., advisory group, coinvestigator) stood out as better able to manage different viewpoints. Teams adjusted engagement structures and behaviours to facilitate an overall culture of inclusion and respect. Partners acknowledged the intentional efforts of researchers to incorporate their perspectives, navigate challenges and communicate the value of partner input. Conclusion By using collaborative decision‐making in the early stages and throughout the study, researchers built trust with partners so that when decisions were difficult to resolve, partners still felt listened to and that their input mattered. Patient or Public Contribution Members of the PCORI Patient Engagement Advisory Panel in 2019–2020 provided input into the design of the study, including the research questions and approaches to data collection and analysis.